TOTAL FLAVONOID CONTENT ANALYSIS OF RAMANIA LEAVES’ EXTRACT USING ETHANOL, METHANOL AND N-HEXANE AS SOLVENTS (Research report) - Risa Hermalinda; Irham Taufiqurrahman; Zairin Noor Helmi (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Wound healing process consists of three phases: inflammation, proliferation, maturation and remodelling. Secondary metabolites are chemical compounds that have potential to be explored and developed in search of raw materials for drugs to assist wound healing process; one of them is flavonoid. Flavonoid is classified as natural phenolic compound that has antioxidant properties coexisted with its antimicrobial and anti-inflammatory effect. Flavonoid is usually available in the form of glycosides and soluble in polar solvents, such as methanol and ethanol. The bark and leaves of Ramania, a native plant of Kalimantan, contains flavonoid compound with non-optimal utilization of its potential. Purpose: To determine the differences in total flavonoid content of Ramania leaves’ extract obtained using ethanol and methanol solvents. Methods: This study is a true experimental study using post-test only with control group design; Samples collection were comprised of 27 specimens, categorized into three groups: two treatment groups using 70% ethanol solvent, one group using 70% methanol solvents, and one control group using 70% n-hexane solvent. Results: There were significant differences between ethanol group and methanol group result (p<0.05); ethanol group and n-hexane group result (p<0.05); and methanol group and n-hexane group result (p<0.05). Conclusion: This study concluded that there were significant differences in the total flavonoid content of Ramania leaves’ extract using ethanol and methanol as its solvents.